The proportion and associated factors of private health insurance uptake in the East Coast Malaysia - Abd Khalim, Mohd Adli (2021)
Background: The public healthcare system in Malaysia is overburdened, underfunded, and unsustainable. There is a need to rethink healthcare financing through PHI by increasing its uptake which will assist in reducing the burden of the public healthcare system and lower the level of household OOP expenditure. Objective: This study aimed to study the proportion of PHI uptake and its associated factors among the East Coast population. Methodology: A cross-sectional study was done from February 2021 until June 2021 using a bilingual web-based proforma among the East Coast population. Proportionate stratified sampling was done to obtain 1113 respondents from the East Coast region of Peninsular Malaysia. Descriptive analysis and logistic regression were applied. Result: All 1138 respondents who fulfilled the study criteria were included. The proportion of PHI uptake among the East Coast population was 54.3%. Pahang had the highest PHI uptake at 21.3%, followed by Kelantan (21.1%) and Terengganu (12.0%). Factors associated with PHI uptake in the East Coast region were education level (AdjOR: 1.82, 95% CI: 1.26, 2.64), household income categories for both M40 (AdjOR: 2.34, 95% CI: 1.73, 3.17) and T20 (AdjOR: 3.50, 95% CI: 2.40, 5.10), and employment status including working in public sector (AdjOR: 6.76, 95% CI: 3.26, 14.01), private sector (AdjOR: 7.28, 95% CI: 3.36, 15.79), and self-employed (AdjOR: 10.34, 95% CI: 4.39, 24.38). Conclusion: The proportion of PHI uptake among the East Coast populations in the current study was higher (54.3%) than the total proportion of PHI uptake among the East Coast populations reported in the National Health and Morbidity Survey 2019 (31.6%). Significant factors associated with the uptake of PHI were those that reflect the ability-to-pay, which reaffirmed the fact that PHI should be promoted among those who can afford it. The findings may benefit PHI providers to introduce insurance policies that may attract more potential clients. However, policymakers should also monitor these developments to better protect the rights of PHI purchasers in Malaysia.